Study of the Copper, Chromium, Manganese and Zinc Contents in the Species Azorella spinosa (Apiaceae), Collected in the Maule Region, Chile - Tapia, Jaime; J. Cornejo; Gutiérrez, Margarita; Peñailillo, Patricio; Baettig, Ricardo; Vargas‐Chacoff, Luis; Espinoza, Jessica; San Martin Barrientos, Aurelio Del Carmen (My University, 2019)
The increase in prevalence of environmental pollution, especially soil contamination with toxic metals has led to their uptake in the human food chains through plant parts. Accumulation and magnification of heavy metals in human tissues through comsuption of herbal medicine can cause hazardous impacts on health. Therefore, chemical profiling of four heavy metals (Cu, Cr, Mn and Zn) was undertaken in samples of Azorella spinosa from coast and mountain of Maule Region in Chile. The Cu, Cr, Mn and Zn concentrations were determined in plants of the species Azorella spinosa and their soils of origin. For each plant, the metal contents in the stalk, leaves and soil were determined by flame atomic absorption spectroscopy. The methodology was validated using certified reference material: BIMEP-432 for the plant samples and MESS-1 for the soil samples. The concentration ranges found in the plant tissue were: Cu: 1.2 - 62.5; Cr: 0.2 - 3.2; Mn: 188.6 - 1345.1 and Zn: 7.5 - 55.9 mg·kg-1 (dry weight). For the soil samples, the ranges were: Cu: 6.4 - 81.5; Cr: 4.6 - 50.4; Mn: 335.6 - 1936.1 and Zn: 15.6 - 65.9 mg·kg-1 (dry weight). The results were evaluated statistically (two-way ANOVA) to correlate the Cu, Cr, Mn and Zn concentrations in Azorella spinosa plant tissues with those in the soil samples from the corresponding sampling areas.
Keywords: Dry weight